Review: A Modest Approach of Electrochemical Sensor to Determine Biogenic Amines in Food and Beverages - Muhammad Abdurrahman Munir; Badri, Khairiah Haji; Heng, Lee Yook; Inayatullah, Ahlam; Badrul, Hamid Alkhair (PUSAT SAINS INDONESIA, 2020)
Biogenic amines are chemical compounds that can be found in protein food. The analysis of biogenic amines in food samples is very important because the toxicity released by them is very adverse if consumed by human. Several methods have been applied and developed in order to detect biogenic amines such as liquid chromatography (LC) and gas chromatography (GC). Nevertheless, both of them are time consuming and using many chemical compounds. Thus, electrochemical sensors become the best solution in order to solve the issues from chromatography methods. Electrochemical sensors are very simple, easy to use and cheap. This paper reviews about various techniques of electrochemical sensor such as chemical sensors, biosensors and optical sensors that have been used for biogenic amines detection.